Three new species of Patrus Aubé with additional records of Gyrinidae from China (Coleoptera, Gyrinidae) - Liang, Zulong; Angus, Robert B.; Jia, Fenglong (European Journal of Taxonomy, 2021)
Three new species of Patrus Aubé, 1838 are described from China: Patrus hainanensis sp. nov. from Hainan; Patrus jiangxiensis sp. nov. from Jiangxi; Patrus shangchuanensis sp. nov. from Guangdong. Eight species / subspecies of Gyrinidae are recorded from China for the first time: Metagyrinus vitalisi (Peschet, 1923), Orectochilus argenteolimbatus Peschet, 1923, Orectochilus murinus Régimbart, 1892, Patrus haemorrhous (Régimbart, 1892), Patrus marginepennis angustilimbus (Ochs, 1925) from Yunnan; Patrus coomani (Peschet, 1925) from Guangdong; Patrus procerus (Régimbart, 1884) from Guangxi; Patrus annandalei (Ochs, 1925) from Hainan. Additional faunistic data of Gyrinidae from China are provided. A key to Chinese species of Patrus Aubé based on examined specimens from China is given.